Dimensões do ensino das tecnologias digitais da informação e comunicação na área da matemática: uma análise a partir das competências e habilidades da BNCC. - (:unkn) unknown (UNIVERSIDADE FEDERAL DO OESTE DO PARÁ, 2024)
Digital Information and Communication Technologies (DICT) are increasingly present in people's reality. Therefore, it is necessary to train digitally competent citizens who know how to deal with DICT in a critical, ethical and responsible way. Studies related to essential learning in DICT are increasingly relevant, considering that these have been evolving at an accelerated pace in recent years. In Brazil, there is the National Common Curricular Base (BNCC), which is a normative document that guides essential learning in basic education; Among these learnings, there are those focused on DICT and computing. Given this, this study set out to answer the following question: How do BNCC skills and abilities in elementary school – final years – and high school guide learning in DICT in the area of mathematics? The main objective of the work is to analyze and categorize the skills and abilities related to DICT in the area of mathematics within the BNCC, taking as analysis support the dimensions of learning related to training in DICT and computing, highlighted in the BNCC, taking into account the role that these play in contemporary society. Yin's (2016) qualitative research analysis method was used, consisting of five phases: Compilation, decomposition, recomposition, interpretation and conclusion. The analysis was organized around three categories: a) digital culture, b) digital technology and c) computational thinking. The results demonstrated that digital culture has little emphasis, given the little recurrence between skills and abilities, as learning in DICT focuses on solving problems and representing data in digital environments. The results obtained in this study can contribute to future studies on this same topic, not limited to the area of mathematics, both theoretically and practically, and indicate the need for greater emphasis on training in DICT in undergraduate courses.
Keywords: TDIC; BNCC; Matemática; Competências; Habilidades; CIÊNCIAS EXATAS E DA TERRA